Risk factors and preventable strategies of ventilator-associated pneumonia: the role of nursing care and epidemiological surveillance - Marta Wałaszek; Elżbieta Rafa; Małgorzata Kołpa (Termedia Publishing House, 2022)
Mechanically ventilated patients are at risk of several complications, including ventilator-associated pneumonia (VAP). VAP is the most common nosocomial infection in this group of hospitalized patients. As a nosocomial infection, it is an undesirable event and is associated with prolonged hospitalization, high costs, and high mortality. To minimize the incidence and provide safe care for mechanically ventilated patients, it is recommended that VAP prevention procedures be developed and implemented, which take into account the general principles of infection prevention such as hand hygiene, isolation, and personal protective equipment, as well as risk factors associated with the treatment, which include, among others, patient position, nutrition, oral hygiene, and tracheobronchial toilet. Knowledge of ventilator operation and decontamination of medical equipment are also of great importance in the prevention of VAP. Collaboration between the patient care staff and the and the infection control team is equally important. Effective VAP surveillance systems can significantly reduce the risk of its occurrence. The aim of this study is to present the issues of VAP with particular emphasis on risk factors for the disease, nursing care, and epidemiological surveillance on the basis of a literature review. The work is dedicated to both epidemiological nurses employed in infection control teams and nurses working in intensive care units, where patients requiring mechanical ventilation are hospitalized, as well as representatives of other professions (e.g. physiotherapists, nutritionists) taking care of patients hospitalized in intensive care units (ICUs).